PEMANFAATAN KOTORAN SAPI SEBAGAI SUMBER ENERGI ALTERNATIF PENGGANTI GAS LPG PADA KOMPOR DI WONOSALAM JOMBANG - Anton Breva Yunanda; Gede Sarya; Bantot Sutriono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Unpleasant smell of dung fly everywhere, debris scattered everywhere afactor peyebab emergence of social upheaval for people around cattle farms.Bio gas reactor tubular closed can be used for cattle dung so it no longerscattered and the scent is not pleasant is already isolated. Not only that biogasproduced can be used together with the community around the farm, which inturn not only relieve social turmoil but rather strengthen the social fabric. Nowthey jointly care for and maintain the reactor in order to benefit together. Builtbio gas reactor is fixed dome models (fixed dome) with a capacity of 10 m3 ofmanure. It means being able to accommodate dirt 10-15 adult cattle. After 60days of curing inside the reactor tube, it turns out this bio gas reactor capableof producing enough gas used for cooking purposes 15 families around the farmtogether.Keywords: degister, biogas, cattle farm